ANÁLISE DO AUTOCUIDADO ANTES E APÓS APLICAÇÃO DO INVENTÁRIO PORTAGE EM UMA CRIANÇA COM SÍNDROME DE DOWN - Brancaccio, Vanessa Fernanda; Manzini, Eduardo José (UNESP, 2020)
The study evaluated the development in relation to the self-care of a child with Down Syndrome,aged two years and seven months, attended at one Specialized Rehabilitation Center using theOperational Portage Inventory. After the evaluation, the subject was followed up for threemonths, and after the intervention, performed by the health professional, a second evaluationwas performed. It was analyzed that the child who before the intervention performed only threeof the twelve activities for the age of one to two years and four of twenty-seven activities for theage of two to three years, presented improvements with the physiotherapy, being significant forthe range of one to two years, since he was able to carry out the twelve proposed activities; andnot performing significantly for the age group of two to three years. After analyzing the activitiesthat the child was able to perform, a proposal was made for intervention in the physiotherapyarea for the activities that the child could not perform. This concludes that there are few studiesfound in the literature regarding down syndrome and self-care. And physiotherapy and other health area are based on the acquisition of activities of daily living in children with SD toprovide these children with greater independence during day to day activities. Received on: 18/12/2019 Reformuleted on: 20/12/10 Accepted: 20/12/10